Dodeca satellite: a conserved G+C-rich satellite from the centromeric heterochromatin of Drosophila melanogaster. - Abad, J P (1992)
To identify sequences from the centromeric region, we have constructed a Drosophila melanogaster yeast artificial chromosome (YAC) library and screened it with purified DNA from the minichromosome Dp(1;f)1187 derived from the X chromosome. We describe the structure of one clone isolated in this way. This YAC is structurally unstable and contains tandemly repeated G+C-rich 11-mer and 12-mer units, which we call dodeca satellite. Most of this satellite is located near the centromere of an autosome. Cross-hybridizing sequences are found in the genomes of organisms as distant as Arabidopsis thaliana and Homo sapiens.